Bending fatigue of single-wall and double-wall corrugated paperboards under sinusoidal and random loads. (February 2022) - Wang, Zhi-Wei; Lai, Yang-Zhou; Wang, Li-Jun
The bending fatigue tests of single-wall and double-wall corrugated paperboards were conducted to obtain the ε rms – N curves under sinusoidal and random loads in this paper. The ε rms – N equation of corrugated paperboard can be described by modified Coffin–Manson model considering the effect of mean stress. Four independent fatigue parameters are obtained for single-wall and double-wall corrugated paperboards. The ε rms – N curve under random load moves left and rotates clockwise compared with that under sinusoidal load. The fatigue life under random load is much less than that under sinusoidal load, and the fatigue design of corrugated box should be based on the fatigue result under random load. The stiffness degradation and energy dissipation of double-wall corrugated paperboard before approaching fatigue failure are very different from that of single-wall one. For double-wall corrugated paperboard, two turning points occur in the stiffness degradation, and fluctuation occurs in the energy dissipation. Different from metal materials, the bending fatigue failure of corrugated paperboard is a process of wrinkle forming, spreading, and folding. The results obtained have practical values for the design of vibration fatigue of corrugated box.